Phenol degradation of biofilm formed by bacterial strain isolated from oil polluted water samples collected in Vung Tau - Nhi Cong, Le Thi; Trung, Trinh Thanh; Ngoc Mai, Cung Thi; To Uyen, Do Thi (Academia Journal of Biology, 2016)
Phenol and phenolic compounds are found as major pollutants in various types of environmental sites. They exist in industrial wastewater of oil reﬁneries, and petrochemical and phenol resin industry plants. To remove these components, using biofilm-forming microorganisms is new approach currently. From isolated bacteria which could degrade diesel oil and several hydrocarbon components containing in crude oil, we selected the strain VTPG5 having capacity of biofilm formation and phenol utilization. Comparing of the part of 16S rRNA of the strain with bacterial strains in NCBI and LNSP by using specific primer pair 9f and 1525r, this strain belonged to the genus Rhodococcus then was named Rhodococcus sp.VTPG5. The gene was registed in Genbank NCBI with accession number LC057207. The optimal conditions to form biofilm of the strain after 48 hours were elucidated as 37oC, pH 7, 1.5% of NaCl with glucose and (NH4)2SO4 as carbon and nitrogen sources, respectively. These optimal biofilm-forming conditions were conducted to investigate phenol degradation capacity. As the result, the phenol degradation productivity of the biofilm formed by VTPG5 was 99.8% after 7 day-incubation with the initial concentration of 200 mg/l. The result gave a hint to apply the biofilm formed by VTPG5 to remove phenol and phenolic compounds from waste-water.